Indicators of isokinetic dynamometry of the hip muscles in athletes with patellofemoral pain syndrome after complex correction procedure - E. Prokhorova; V. Arkov (National Electronic Information Consortium (NEICON), 2020)
Objective: to compare the strength of the hip muscles before and after a complex correction procedure for the neuromuscular apparatus of the lumbosacral spine and lower limb in athletes with patellofemoral pain syndrome. Materials and methods: 40 athletes 18-35 years old (mean age -27±6.5 years (M±m)) participated in a randomized control trial. Chondromalacia patellae confirmed by traumatologist was the inclusion criteria. Methods: isokinetic dynamometry. Results: an increase in the strength of the quadriceps muscle and the hamstring muscles at low, medium and high speeds of isokinetic dynamometry was registered after the course of treatment. The study group with exercises for stabilizing the lumbosacral spine and lower limb showed higher strength indices than the control group with exercises for training the muscles of lower limb alone. Conclusions: inclusion of complex correction procedure in the rehabilitation program for athletes with patellofemoral pain syndrome in comparison with the traditional method of therapeutic gymnastics allows to increase the maximum arbitrary force and the endurance of the quadriceps, to improve the neuromuscular capabilities of the quadriceps.